1998
DOI: 10.1046/j.1365-201x.1998.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of red blood cell hyperaggregation on the rat microcirculation blood flow

Abstract: This study presents the effects of red blood cell (RBC) hyperaggregation on the blood flow and pressure in the rat mesentery and cremaster network. We exclusively studied in situ non-vasodilated organs, in order to maintain the physiological regulation mechanisms. Dextran 500 was injected at different concentrations to increase RBC aggregation. The aggregation rate was measured on very small blood samples with an erythroaggregameter (SEFAM) which evaluated the disaggregating shear stress (tau D) needed to brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 26 publications
4
24
2
Order By: Relevance
“…Most previous studies on the effects of RBC aggregation on in vivo blood flow dynamics have utilized models based on including or infusing highmolecular-weight material such as dextrans in the suspending medium (6,18,33). This approach results in increased suspending phase viscosity in addition to enhanced RBC aggregation (e.g., the Dextran group).…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies on the effects of RBC aggregation on in vivo blood flow dynamics have utilized models based on including or infusing highmolecular-weight material such as dextrans in the suspending medium (6,18,33). This approach results in increased suspending phase viscosity in addition to enhanced RBC aggregation (e.g., the Dextran group).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies designed to assess the hemodynamic effects of RBC aggregation, high-mass-weight polymers such as 500-kDa dextran have been used to increase RBC aggregation (6,11,19,35,48). The use of these large polymers has been proven to be effective for modifying RBC aggregation, yet has potential disadvantages: 1) plasma or suspending phase viscosity is increased [e.g., for 500-kDa dextran, 1.5 g/dl yields a 80% increase of suspending medium viscosity (43)] and hence the fluid viscosity near the vascular wall is modified; 2) plasma proteins are diluted via the added polymer solution; 3) in some experimental animals (e.g., the rat), dextran and similar polymers can lead to anaphylactic-type reactions and thus induce a pathophysiological state (10); 4) the elevated colloid osmotic pressure caused by macromolecules in solution could alter intra-versus extravascular fluid volumes; and 5) due to metabolism/excretion, polymer concentration decreases with the time after infusion (22), thus precluding long-term temporal studies of RBC aggregation effects.…”
Section: Discussionmentioning
confidence: 99%
“…7 Another study also confirmed the influence of the RBC hyperaggregability on the microcirculation blood-flow. 8 Other authors suggest that an increase in RBC aggregation influences venous vascular resistance 9 and predisposes to circulary stasis 10 and thrombosis. 11 The aim of this study was to investigate red blood cell aggregability and deformability among obese patients who were qualified for bariatric surgery and its correlation with lipid plasma concentrations.…”
Section: Introductionmentioning
confidence: 99%